2006
DOI: 10.1152/ajpendo.00099.2006
|View full text |Cite
|
Sign up to set email alerts
|

The release of GLP-1 and ghrelin, but not GIP and CCK, by glucose is dependent upon the length of small intestine exposed

Abstract: Previous observations suggest that glucagon-like peptide-1 (GLP-1) is released into the bloodstream only when dietary carbohydrate enters the duodenum at rates that exceed the absorptive capacity of the proximal small intestine to contact GLP-1 bearing mucosa in more distal bowel. The aims of this study were to determine the effects of modifying the length of small intestine exposed to glucose on plasma concentrations of GLP-1 and also glucose-dependent insulinotropic peptide (GIP), insulin, cholecystokinin (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 46 publications
(53 reference statements)
5
88
2
Order By: Relevance
“…However, GHR production is partly mediated by lower intestinal osmolarity and insulin concentrations, not just the presence of nutrients in the stomach or duodenum (Cummings, 2006). Indeed, we found that GHR and insulin concentrations were inversely correlated, purporting previous findings for a role of insulin in the prandial suppression of GHR (Blom et al, 2005;Little et al, 2006). It has also been suggested that GHR may play a role in the adipocyte regulation of glucose homoeostasis through the direct potentiation of insulin-stimulated glucose uptake (Patel et al, 2006).…”
Section: )supporting
confidence: 70%
See 2 more Smart Citations
“…However, GHR production is partly mediated by lower intestinal osmolarity and insulin concentrations, not just the presence of nutrients in the stomach or duodenum (Cummings, 2006). Indeed, we found that GHR and insulin concentrations were inversely correlated, purporting previous findings for a role of insulin in the prandial suppression of GHR (Blom et al, 2005;Little et al, 2006). It has also been suggested that GHR may play a role in the adipocyte regulation of glucose homoeostasis through the direct potentiation of insulin-stimulated glucose uptake (Patel et al, 2006).…”
Section: )supporting
confidence: 70%
“…Mourot et al (Mourot et al, 1988) demonstrated an inverse relationship between gastric emptying half-time and the magnitude of the glycemic response to four foods: potatoes, bread, rice and spaghetti. In this study, the higher profile of CCK on the low GI diet may therefore be attributable to a slower rate of gastric emptying and hence entry of carbohydrate and other macronutrients into the proximal small intestine (o60 cm (Little et al, 2006)). This may prolong stimulation of I cells, which in turn may further decrease gastric emptying and maintain higher CCK production.…”
Section: )mentioning
confidence: 72%
See 1 more Smart Citation
“…In the traditional view, the proximal intestine contains I-cells, which secrete CCK, and GIP-releasing K-cells, while L-cells cosecrete PYY and GLP-1 and are located mainly in the distal intestine (Little et al 2006). However, recent work has challenged these classical views, as individual enteroendocrine cells have been shown to express a variety of gut peptides (Egerod et al 2012, Grunddal et al 2016, while the proximal small intestine has been shown to secrete significant amounts of GLP-1 (Theodorakis et al 2006).…”
Section: Gut Peptide Signalling In Regulating Glucose Metabolismmentioning
confidence: 99%
“…Additionally, colon resection results in further depletion of energy as studies have shown that the colon can absorb up to 15% of energy requirements [40][41]. Furthermore, patients with end-jejunostomy display increased gastric emptying and intestinal transportation [42] due to the lack of the protective effect of hormonal mediators such as GLP-1 GLP-2, and peptide YY [23]. Studies in adults have shown that the presence of little or no colon and less than 50-100 cm of jejunum results in permanent parenteral nutrition [43,44].…”
Section: Pathophysiological Consequences Of Psbsmentioning
confidence: 99%